2021
DOI: 10.3390/bdcc5040058
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Datasets of Surface Roughness for Constructing Big Data from the Context of Smart Manufacturing and Cognitive Computing

Abstract: In smart manufacturing, human-cyber-physical systems host digital twins and IoT-based networks. The networks weave manufacturing enablers such as CNC machine tools, robots, CAD/CAM systems, process planning systems, enterprise resource planning systems, and human resources. The twins work as the brains of the enablers; that is, the twins supply the required knowledge and help enablers solve problems autonomously in real-time. Since surface roughness is a major concern of all manufacturing processes, twins to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To ensure a digital twin function well, Fattahi et al [53] suggested having humancyber-physical system-friendly BD that are easily accessible and understandable for both humans and machines. They also proposed a method for preparing the BD dataset, divided into four segments for easy integration with the digital twin's input, modeling, simulation, and validation modules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To ensure a digital twin function well, Fattahi et al [53] suggested having humancyber-physical system-friendly BD that are easily accessible and understandable for both humans and machines. They also proposed a method for preparing the BD dataset, divided into four segments for easy integration with the digital twin's input, modeling, simulation, and validation modules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors see the Cognitive DT model as one of the enablers and facilitators of the creation of the Federation of Twins. The semantic tools (such as ontologies and graph databases) bring to the DT a more human-like method [30] of processing data and information. This article empowers the need for research in the field of cognitive DT, thus contributing to the field of cognitive computing.…”
mentioning
confidence: 99%